ANALYSIS OF DYNAMIC MODEL OF SHIPPING INCOME TARIFF SYSTEM FOR SHIPPING EXPEDITION SERVICES - Nurlaela Kumala Dewi (Organisasi Kreatif Indonesia Emas, 2024)
The expedition service company PT.XYZ Bandung and Jakarta Branches is facing a decrease in the number of shipments and the weight of goods sent for the Jakarta - Bandung shipping route, which automatically affects the income received. This decline phenomenon can certainly have an impact on the financial condition and sustainability of the company. This study will try to conduct a trial by calculating using a system dynamics model. In previous studies, the tariff determination model was completed using the standard costing method, the actual costing method, the activity based costing method, calculating factory overhead costs, the full costing method and variable costing. The results of the study show that the model with system dynamics is better by showing that the model conditions allow the company PT.XYZ to understand the interactions between variables that form the structure of this model. The model shows the causal relationship between various variables to each other in the model, so that the causal relationship between these variables forms a dynamic system model for the operational model of shipping goods at PT. XYZ Branch Hub Bandung City. The company can understand the interactions of various business elements that occur and can analyze what factors form this model including the shipping of goods, the company's income and profit, and the company's operational costs.